Qua Vadis the Quality of Online Scientific Journal Publishing in State Islamic University (PTKIN) - Erie Hariyanto (Program Studi Ilmu Perpustakaan UIN Alauddin, 2016)
The main problem of scientific journals development among Islamic colleges, both PTKIN and PTKIS, is a matter of managerial capacity or management of a scientific journal. During this time, it iss recognized that the spirit of journal publishing is high, but it ss not followed by managerial skills. It means there were a lot of publishing institutions that publish scientific journals but could not continue well, therefore these published journals considered as only a memorial thing and introduction, moreover there is an obligation to publish an online journal and accreditation instrument that also conducted by online through the portal of ARJUNA DIKTI that becomes opportunity and challenge for managers of scientific journals in the colleges both human resources and infrastructure. This article tries to answer how the position, potention and opportunities PTKIN’s journals in the online journal era